1983
DOI: 10.1007/bf00734843
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the congenital epulis

Abstract: This report presents the ultrastructural features of a congenital epulis. The granular cells of the epulis were packed with numerous membrane bound cytoplasmic granules containing particles, small vesicles, and electron-dense materials. These granules were negative in immunohistochemical reaction for CEA (DAKO PAP KIT). Cytoplasmic organelles such as mitochondria, rough surfaced endoplasmic reticulum, and Golgi apparatus, were absent. Nuclei were markedly indented. Occasionally, banded intracellular collagen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Several theories have been proposed, including origins from odontogenic epithelium, fibroblasts, histiocytes, smooth muscle, nerve-related cells, endothelial cells, pericytes, myofibroblasts, and undifferentiated mesenchymal cells (Table 1) [6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In search of the origin of the granular cells, numerous epithelial, myogenous, neurogenous, neuroendocrine, vascular, fibroblastic, histiocytic, and hormonal immunostains have been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Several theories have been proposed, including origins from odontogenic epithelium, fibroblasts, histiocytes, smooth muscle, nerve-related cells, endothelial cells, pericytes, myofibroblasts, and undifferentiated mesenchymal cells (Table 1) [6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In search of the origin of the granular cells, numerous epithelial, myogenous, neurogenous, neuroendocrine, vascular, fibroblastic, histiocytic, and hormonal immunostains have been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, congenital epulis is characterized by the presence of granular cells as the main tissue components; and ultrastructurally, cytoplasmic organelles of the granular cells are devoid of mitochondria, rough surfaced endoplasmic reticulum and Golgi apparatus, and contain banded intracellular collagen fibers. The histologic origin of granular cells (congenital epulis) has been suggested to possibly be fibroblasts (4,16), mesenchymal cells (10,18,33,46), and epithelial cells (17).…”
Section: Summary Of Results On Lectin Binding and Immunohistochemistrymentioning
confidence: 99%
“…Congenital epulis, or congenital granular cell tumors are rare, pedunculated lesions occurring mostly in the anterior alveolar ridge of the maxilla, and the lesion shows a female predilection (6,10,13,17). The histologic and ultra structural features of granular cells of congenital epulis have been well described in detail (7,10,16,18,19,30,33). Recently, non congenital granular cell tumors (granular cell myoblastomas) have been shown by immunohistochemical means to contain CEA (15,20,29), vimentin (21), S-100 protein (2,3,8,14,25,27,35,36,38,40,45), neuron specific enolase (27) (Figs.…”
mentioning
confidence: 99%
“…The histogenesis of granular cells in congenital epulis has remained enigmatic, in spite of a vast number of immunohistochemical and ultrastructural studies. Several hypotheses have been proposed regarding the origin of the tissue constituting the mass, including one in myocytes, neurocytes, fibroblasts, histiocytes, pericytes, and undifferentiated mesenchymal cells 4,5,7,[9][10][11][13][14][15]21,23,[25][26][27][28]31) . A consensus has yet to be reached, however.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present immunohistological analysis were negative for NSE. The hypothesis that the tissue originates in fibroblasts is supported by the following: shifts were noted between fibroblasts with granules and granular cells; electron microscopy has revealed that granular cells lack a fibroblast-like basement membrane; and some collagenous fibers are engulfed within the protoplasm 10) . According to the histiocyte origin theory, granular cells develop from phagocytic histiocytes that store an abnormal metabolite 26) .…”
Section: Discussionmentioning
confidence: 99%